KEABSAHAN PERJANJIAN AKAN JUAL BELI SEBIDANG TANAH HAK MILIK DALAM PRAKTEK - Jusan Ahmad (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT  That the validity of the sale and purchase that has been declared by the Panel of Judges by taking the example in civil case No. 30 / Pdt.G / 2002 / PN.Smda still premateur. But it has come true in a verdict. Therefore, the party should be defeated or dissatisfied with the verdict, exercising its right to take legal remedy ie the appeal during the court decision has not had permanent legal force (Inkracht Van Gewisjde), after 14 (fourteen) days of the verdict is notified. However, if it has lapsed 14 (fourteen) days after the award is given to the defeated party but not exercised its right, the court decision shall be deemed to have permanent legal force (Inkracht Van Gewisjde). That the legal force of the sale and purchase agreement regardless of the principle of freedom of contract as stated in article 1338 Civil Code can not be said to have the power of law. But it has become a reality, the legal power of the sale and purchase agreement as in this case to be said the legal power of the sale and purchase agreement depends on the validity that has been decided by the court. As to the fact as has been decided by the court that it was a sale and purchase agreement has been strengthened and declared legally valid. Therefore, inevitably the sale and purchase agreement between Defendant I and Defendant II was canceled.